Perancangan E-Book Interaktif sebagai Media Informasi Koleksi: (Studi Kasus: Museum Sandi) - Eneng Wulan Sari; Suhadi Parman; Rifqi Fahrudin (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Museum is an institution that collects, receives, and studies collections of items that have knowledge and informational value as well as valuable assets. Generally, the items in a museum are solid objects that cannot interact directly with visitors. Therefore, each museum has a special staff, known as museum guides, to accompany visitors in exploring all museum collections. However, not all visitors want to be guided by museum guides, so there is a need for supporting media to help guides manage visitors who do not want to be guided. The media to be created is an interactive e-book. This interactive e-book can help visitors who want to explore the museum independently to obtain information from the museum collections. The e-book contains a menu of content consisting of information about museum collections, images of museum collections, text and audio information about museum collections, and animation illustrations of museum mascots. With a total of 33 pages containing information from 8 museum rooms. This design was made using the ADDIE method and evaluated using UEQ (User Experience Questionnaire) with a result of